2012
DOI: 10.1016/j.dental.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial amorphous calcium phosphate nanocomposites with a quaternary ammonium dimethacrylate and silver nanoparticles

Abstract: Objectives Calcium and phosphate ion-releasing resin composites are promising for remineralization. However, there has been no report on incorporating antibacterial agents to these composites. The objective of this study was to develop antibacterial and mechanically-strong nanocomposites incorporating a quaternary ammonium dimethacrylate (QADM), nanoparticles of silver (NAg), and nanoparticles of amorphous calcium phosphate (NACP). Methods The QADM, bis(2-methacryloyloxyethyl) dimethylammonium bromide (ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
386
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 306 publications
(394 citation statements)
references
References 59 publications
2
386
1
5
Order By: Relevance
“…Recent studies have shown quaternary ammonium dimethacrylate and Ag-NPs to be effective as primers for dental adhesives because of their antibacterial properties and bond strength 8,20) . The main purpose of surface modification of Ag-NPs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown quaternary ammonium dimethacrylate and Ag-NPs to be effective as primers for dental adhesives because of their antibacterial properties and bond strength 8,20) . The main purpose of surface modification of Ag-NPs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that quaternary ammonium salt (QAS) moieties can affect the viability of Gram-positive and Gram-negative bacteria due to positive charges that exert a strong electrostatic interaction with negatively charged bacteria [25][26][27]. Therefore, the positive charge density of QAS antimicrobial agents plays a key role in their antimicrobial performance.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%
“…In 2006, a research developed by Beyth et al 24) reported that 1 wt% quaternary ammonium polyethyleneimine (QPEI) nanoparticles immobilized into composite or fluid resin had strong antimicrobial activity upon contact without leach-out of the nanoparticles and compromising in mechanical properties. Cheng et al [25][26][27] performed studies incorporating of nanoparticles of amorphous calcium phosphate (NACP), quaternary ammonium dimethacrylate (QADM), and nanoparticles of silver (NAg) into composite resins. The results had shown that modified resins greatly decreased biofilm metabolic activity, colony-forming unit (CFU), and lactic acid with strong and durable antimicrobial properties and remineralization, while matching the load-bearing capability of commercial composites without antimicrobial properties.…”
Section: Composite Resinmentioning
confidence: 99%
“…It has been shown that there is microleakage on restoration margins, and these gaps can be colonized by oral bacteria, thus resulting in secondary caries, which makes the restoration replacement necessary 22,23) . In order to prevent or diminish biofilm accumulation over composite and in the restorations margins, and also to improve the durability of prostheses, antimicrobial restorative materials have been developed, especially through the incorporation of quaternary ammonium to composite resins [24][25][26][27][28][29][30][31][32] . In 2006, a research developed by Beyth et al 24) reported that 1 wt% quaternary ammonium polyethyleneimine (QPEI) nanoparticles immobilized into composite or fluid resin had strong antimicrobial activity upon contact without leach-out of the nanoparticles and compromising in mechanical properties.…”
Section: Composite Resinmentioning
confidence: 99%